Social disconnection correlates of a “Wish to Die” among a large community-dwelling cohort of older adults - Ward, Mark; Briggs, Robert; Kenny, Rose Anne (Frontiers in Public Health, 2024)
Introduction: Social disconnection and deaths by suicide among older adults are both important public health concerns, particularly in the context of ageing populations. The association between death ideation and behaviours, and social disconnection is well established and both functional and structural social relationships have been identified as predictive of suicide-related thoughts and behaviours. The 'Wish to Die' (WTD) involves thoughts of or wishes for one's own death or that one would be better off dead is a commonly used indicator to capture death ideation. It has been shown to be as predictive as active ideation of future suicide attempt.Methods: Data were from a large cohort of community-dwelling older adults aged 50+, The Irish Longitudinal Study on Ageing (TILDA). Cross-sectional analyses of the association between numerous markers of social disconnection (loneliness, social isolation, living alone, marital status, social participation, volunteering, and attending religious service) and WTD were conducted.Results: Multiple markers of social disconnection were associated with a 'wish to die'. However, loneliness was the strongest risk factor while attendance of religious services was an important protective behaviour.Discussion: There is a strong association between social disconnection and a WTD among older adults. There is also a strong association between depression and a WTD, while attending religious services or similarly prosocial settings may protect older adults from experiencing negative thoughts about dying.